Clinical, CT profile of wistar rats receiving therapeutic doses of alendronate alone and in combination with cyclophosphamide and dexamethasone - David Bienvenue Ntep Ntep; Jean Claude Mballa Amougou; Jules Julien Ndjoh; Brian Zilefac Ngokwe; Emmanuel Nnanga Nga; Charles Bengondo Messanga (Elsevier, 2022)
Introduction: The exact pathogenesis of drug-induced osteonecrosis of the jaw is still unknown. The aim of this study is to develop a reliable rat model of alendronate-related osteonecrosis of the jaw and to determine the CT profile of bisphosphonate-induced osteonecrosis of the jaw. Materials and methods: 98 Wistar rats were divided into 4 groups. Rats in the test groups received, in addition to 0.05 mg/kg alendronic acid orally (twice a week for 8 consecutive weeks), 1 mg/kg/day subcutaneously of dexamethasone for 2 weeks and 150 mg/kg cyclophosphamide orally twice and once a week before and after dental avulsion. Results: From week 4 to week 8 after drug administration, the frequency of stage 3 osteonecrotic lesions increased in the test groups from (G1 = 5 (18.5%); G2 = 11 (39.2%); G3 = 6 (21.4%)) to (G1 = 8 (32%); G2 = 12 (42.8%); G3 = 13 (46.4%)) respectively. However, healing was not impaired in the control group (p = 0.003).Scannographic analysis showed that the difference in bone mineral density was greater in rats exposed (G2 = 486.22 ± 94.76; G3 = 584.9 ± 42.47) to the drug combinations than in rats exposed (G1 = 421.61 ± 125.81) to alendronate alone. Conclusion: Based on this study, the rat treated with alendronate in combination or not with dexamethasone and cyclophosphamide and dental extraction can be considered as a new, reliable and reproducible model to better understand the pathophysiology of osteonecrosis of the jaws in the context of osteoporosis and prostate cancer. Furthermore, bone mineral density has been shown to be an important diagnostic criterion.